Pengaruh Kualitas Produksi dan Pemasaran Terhadap Kepuasan Konsumen pada Usaha Cecek Kulit Sapi Skala Rumah Tangga - Adi Prasetyo Nugroho; Yogi Yunanto; Andy Chandra Pramana (MES Bogor, 2026)
This study aims to determine and analyze the influence of production quality and marketing on consumer satisfaction at Bu Anik Cowhide Cecek Business in Kediri, both partially and simultaneously. The research method used is descriptive quantitative associative by distributing questionnaires to 100 respondents selected using accidental sampling technique at Mrican Market, Kediri. The obtained data were processed using SPSS software through a series of research instrument tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing via t-test and F-test. The regression analysis results show that partially, the production quality variable has a positive and significant effect on consumer satisfaction. Similarly, the marketing variable is proven to have a positive and significant effect on consumer satisfaction partially. Simultaneously, both independent variables significantly affect the buyer satisfaction level with an F-value of 45.321. Through the coefficient of determination test, it was found that the variation in consumer satisfaction is influenced by 48.3% by production quality and marketing, while the remaining 51.7% is influenced by variables outside the scope of the regression model in this study.